LegalTech w kancelarii komorniczej - Maciejewska, Klaudia (Wydawnictwo C.H. Beck, 2022)
Transformational technologies are used to digitize the work of court bailiffs. They are a way to increase the effectiveness, productivity, and efficiency of legal processes. A modern bailiff cannot function without the support of information systems, ICT systems, or expert systems. The author presents the organization of the work of bailiff offices, the possibilities offered by LegalTech, and the possibilities of using IT tools in the work of bailiff offices. Particular attention was paid to the security of personal data processed in bailiff offices, the security measures applied, and security management. The article aims to indicate that the implementation of LegalTech in bailiff offices is a must. It is a challenge related to increased investments, reorganization of the offices’ operating model, the search for efficiency in working time, or the security of personal data processing, and requires the recognition of risk analysis, accountability, and protection of professional secrecy.
Keywords: artificial intelligence; new technologies; bailiff’s office; bailiff; LegalTech; enforcement proceedings; personal data protection; digitization